DETERMINAN KINERJA PEGAWAI DENGAN LINGKUNGAN KERJA SEBAGAI PEMODERASI PADA PENGELOLA PEMANFAATAN BARANG MILIK DAERAH DI LINGKUNGAN DINAS PENDIDIKAN KOTA SEMARANG - Arifin Rasyid; Kesi Widjajanti; Djoko Santoso (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2022)
This study is a quantitative study that aims to determine the effect of work environment moderation on the determination of employee performance, namely workload, competence and teamwork in the Semarang City Education Office.The sample population that is the object of the study is the manager of the utilization of regional property using a kretjie table which is then proportionally taken as an equal representation of the area/region. Sources of data obtained by questionnaires and collection with google.form. The data analysis of this research used Structural Equation Modeling (SEM) with Partial Least Square as a tool.The results of this study indicate that the work environment moderates the relationship between competence and employee performance significantly. As for the relationship of workload to performance and teamwork relationship to performance, the work environment does not moderate significantly.The implication of this research is that in improving employee performance, there is a need for training in the IT sector and education and training that supports the implementation of the main tasks and functions supported by a comfortable work environment.